2021
DOI: 10.18632/aging.203484
|View full text |Cite
|
Sign up to set email alerts
|

Identification and epidemiological evaluation of gastric cancer risk factors: based on a field synopsis and meta-analysis in Chinese population

Abstract: To summarize and assess the credibility and strength of non-genetic factors and genetic variation on gastric cancer risk, we performed a field synopsis and meta-analysis to identify the risk of gastric cancer in Chinese population. Cumulative evidence was graded according to the Venice criteria, and attributable risk percentage ( ARP ) and population attributable risk percentage ( PARP ) were used to evaluate the epidemiological effect. A total of 956 studies inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Frequent mealtime shifts over a long period increase the risk of H. pylori infection and gastritis [42]. A quantitative analysis of the relationship between irregular eating habits and gastric cancer in China showed that both irregular and fast eating were independent risk factors for gastric cancer (irregular eating: OR = 1.71, 95% CI: 1.62-1.91; fast eating: OR = 1.83; 95% CI: 1.71-2.01) [43]. It is common in Korea to enjoy eating fried chicken with beer as a late-night snack, and such habits could add to the risk of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent mealtime shifts over a long period increase the risk of H. pylori infection and gastritis [42]. A quantitative analysis of the relationship between irregular eating habits and gastric cancer in China showed that both irregular and fast eating were independent risk factors for gastric cancer (irregular eating: OR = 1.71, 95% CI: 1.62-1.91; fast eating: OR = 1.83; 95% CI: 1.71-2.01) [43]. It is common in Korea to enjoy eating fried chicken with beer as a late-night snack, and such habits could add to the risk of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The top 3 to 6 common cancers are gastric, liver, colorectal, and esophageal cancers in Anhui Province, which are infection-related and poverty-related cancers. These cancers are associated with unhealthy lifestyles, such as alcohol consumption, 17 pickled foods, 18 eating hot food, 19 and chronic infectious agents. 20 In order to address this public health concern, the Huaihe Valley Cancer Early Diagnosis and Treatment Program has been providing screening services for upper gastrointestinal and liver cancers in Anhui Province since 2007.…”
Section: Discussionmentioning
confidence: 99%
“…However, antibiotics resistances steadily increase causing the therapy failure rates to keep climbing 2 . H. pylori may directly damage gastric epithelial cells through virulence factors and lead to many related gastric diseases 3 , while the population attributable risk percentage (PARP) of H. pylori was high up to 23.66% according to the epidemiological effect estimation for gastric cancer 4 . Moreover, H. pylori infection has a detrimental impact on the efficacy of cancer immunotherapies 5 .…”
Section: Introductionmentioning
confidence: 99%